Molecular, histological, and anti-oxidant evaluation of colitis induction in rats by different concentration of dextran sodium sulfate (5 KDa) - Noppawat Pengkumsri (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objective: The current study was conceived and performed to assess the pathophysiological, histological, and molecular manipulations of dextran sodium sulphate (DSS; MW: 5,000 Da) intervention in the rat and determined the changes in the antioxidant capacity of host and representative antioxidant enzymes. Methods: Wistar rats were fed with two different concentrations (3 and 5%) of DSS for seven days and caged for another seven days. Then colon and serum samples were collected, and colitis induction was assessed by histochemical examination. The level of antioxidant enzymes were determined by spectroscopy methods, and gene regulations were evaluated by qPCR. Results: The body mass of rat was gradually reduced to DSS intervention compared to naive control. The statistically significant level of reduction in the colon length has been recorded in DSS-treated rats (3% DSS-treated: 14.33±0.53 cm; 5% DSS-treated: 13.73±0.53 cm) compared to control (Control: 17.41±0.54 cm). The total histological scores of different study groups suggested that DSS causes the significant level of damages in rat colon. The antioxidant capacity of the host was significantly reduced in terms of trolox equivalence. About three-fold higher the amount of malondialdehyde was recorded in 5% DSS-treated group compared to control. The content of antioxidant enzymes were drastically reduced (1.4-2.7 fold) upon DSS exposure than naïve control. The expression of selected inflammatory markers (IL-6, TNF-α, and iNOS) was up-regulated in DSS-exposed groups. Conclusion: The current study clearly indicated that DSS altered the expression of selected inflammatory genes, antioxidant capacity, and scavenging enzymes in such a way that it facilitates the development of colitis in Wistar rat and the study provides the necessary information the experimental designing to explore the ability of any active principle against colitis using DSS (5 KDa) induced colitis rat model.